1974
DOI: 10.1042/bj1430419
|View full text |Cite
|
Sign up to set email alerts
|

The role of ribosomal ribonucleic acid in the structure and function of mammalian brain ribosomes

Abstract: In order to resolve the functional role of intact rRNA in polypeptide chain elongation mouse brain ribosomes were treated with dilute pancreatic or T(1) RNAase (ribonuclease). After RNAase treatment, several physical-chemical properties as well as the functional activity of the ribosomes were measured. RNAase treatment resulted in the extensive hydrolysis of both 18S and 28S rRNA; however, the sedimentation properties of mono-ribosomes were unaltered and more than 90% of the relatively low-molecular-weight RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The unaltered appearance of ribosomes from RNase-treated RM suggested that, in spite of the degradation of exposed mRNA and rRNA, the integrity of the bound ribosomes was not greatly affected by the nuclease treatment. We found that, in agreement with previous observations on RNase-treated ribosomes (14,23,31), an intact rRNA was not necessary for peptide bond synthesis since ribosomes aggregated on RNase-treated RM remained functionally capable of coupling puromycin to their nascent polypeptides. This led to an extensive puromycin-dependent release of ribosomal subunits when microsomes containing ribosomal aggregates were analyzed by density FmURE 12 Aggregation of bound polyribosomes on RM treated with antibodies against 60S ribosomal proteins.…”
Section: Discussionsupporting
confidence: 91%
“…The unaltered appearance of ribosomes from RNase-treated RM suggested that, in spite of the degradation of exposed mRNA and rRNA, the integrity of the bound ribosomes was not greatly affected by the nuclease treatment. We found that, in agreement with previous observations on RNase-treated ribosomes (14,23,31), an intact rRNA was not necessary for peptide bond synthesis since ribosomes aggregated on RNase-treated RM remained functionally capable of coupling puromycin to their nascent polypeptides. This led to an extensive puromycin-dependent release of ribosomal subunits when microsomes containing ribosomal aggregates were analyzed by density FmURE 12 Aggregation of bound polyribosomes on RM treated with antibodies against 60S ribosomal proteins.…”
Section: Discussionsupporting
confidence: 91%
“…Ostner & Hultin (1968), who showed that these d both the proteins are relatively sensitive to proteolytic attack al proteins, and that proteolysis results in a loss of ribosomal activity. However, at this time we cannot rule out the possibility that even structural proteins underwent proteolysis and that the resultant peptides remained associated with the ribonucleoprotein particles by the strong RNA-protein interactions that have been shown to confer structural stability to brain ribosomes (Grove & Johnson, 1974). Our results are compatible with those of Terao et al (1974) and Subramanian (1974), who reported a lack of exchange of ribosomal proteins with cytoplasmic preparations from both prokaryotic and eukaryotic cells.…”
Section: Show Thatsupporting
confidence: 86%
“…The rRNA was analysed on polyacrylamide gels as described by Grove & Johnson (1974). Ribosomes were resuspended in electrophoresis buffer (40mM-Tris/HCl, pH7.2, 20mM-sodium acetate, 1.0mM-EDTA, 0.2% sodium dodecyl sulphate).…”
Section: Polyacrylamide-gel Electrophoresismentioning
confidence: 99%
“…Moreover, lower than expected rRNA ratios in other cell types do not necessarily impact protein synthetic capabilities. For example, ribosomes from mouse brain subjected to nucleases maintained greater than 80% function as determined by in vitro translation assays, even when all but 2% of rRNAs were at least partially degraded [32,33]. In addition, rat liver ribosomes were found to retain 30% of their original activity while having negligible amounts of intact 28S rRNA [34].…”
Section: Discussionmentioning
confidence: 99%